Numerical wave tank modelling of regular waves propagation using OpenFOAM - Chai, K. (Institute of Electrical and Electronics Engineers Inc., 2018)
The physical testing of coastal wave/structure interaction is conventionally performed in a wave basin. However, the investigation requires specialized facilities and manufacturing of scaled models which are costly in both time and money. This paper outlines the development of Numerical Wave Tank (NWT) for the Universiti Teknologi PETRONAS (UTP) wave basin as a virtual simulation tool for regular waves propagation using an open-source licensing numerical model waves2FOAM which inherits its basic structure from OpenFOAM in solving the famous Reynolds Averaged Navier Stokes (RANS) equation. The model validation was performed by correlating the simulated NWT wave properties with the actual waves generated by physical experiment under similar input condition and a 1:1 scale. Mesh fineness study was also performed to investigate wave height convergence with varying mesh sizes, which leads to the optimal mesh size with respect to computational time and reliability. It is shown that good correlation was achieved between the wave properties simulated by OpenFOAM and physical experiments. This study demonstrates the viability of developing a reliable virtual wave tank with open source tools which is anticipated to complement its real counterpart in future studies concerning fluid dynamics and fluid-structure interaction. Â© 2017 IEEE.